1978
DOI: 10.1007/bf02533366
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and metabolic studies of distillable fractions from fresh and thermally oxidized corn oil and olive oil

Abstract: A semisynthetic diet containing 15% by weight of dietary fat was fed to six groups of male wistar rats for 28 days. Two groups received the distillable fraction of fresh corn oil (DCO) or fresh olive oil (DOO), two groups the distallable fractions of the thermally oxidized fats (OCO,OOO), and two groups received the respective fresh fats as controls (FCO, FOO). Substantial changes in the fatty acid composition occurred in the fats upon thermal oxidation. Only the rats that received OOO showed overt symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Among the low-molecular-weight compounds, 4-hydroperoxy-2-en-1-al with 5-9 carbons was reported to have the strongest toxicity 21) . Gabriel et al 22) gave Wistar rats fresh olive oil, and distillable fractions of fresh and thermally oxidized olive oil, respectively, and found out that only the rats that received the distillable fraction of thermally oxidized olive oil showed overt symptoms of heated fat toxicity. This was reflected in the histological scores of these animals, with the liver sustaining the most numerous and severe lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the low-molecular-weight compounds, 4-hydroperoxy-2-en-1-al with 5-9 carbons was reported to have the strongest toxicity 21) . Gabriel et al 22) gave Wistar rats fresh olive oil, and distillable fractions of fresh and thermally oxidized olive oil, respectively, and found out that only the rats that received the distillable fraction of thermally oxidized olive oil showed overt symptoms of heated fat toxicity. This was reflected in the histological scores of these animals, with the liver sustaining the most numerous and severe lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Gabriel et al 15) reported that overt symptoms of heated fat toxicity did not develop in the Wistar rats received thermally oxidized olive oil, but in the rats given the distillable fraction of the oil. As described in , the oil heated with gluten had a mild odor, and showed little cytotoxicity in the present study.…”
Section: Diet Oilmentioning
confidence: 99%
“…There is a large number of works evaluating the short-and long-term effects of the use of extremely overheated fats and oils, mainly in laboratory animal diets (e.g. in rats: Crampton et al, 1953;Gabriel et al, 1978;Eder and Kichgessner, 1999), but there is a lack of sufficient knowledge about the dietary use of recycled frying oils at commercial feed levels in livestock animals to assess their impact on animal performance, health and well-being.…”
Section: Introductionmentioning
confidence: 99%